CdS-Ti3C2Tx-BME composite photocatalyst as well as preparation method and application thereof
By using β-mercaptoethanol (BME) in the CdS-Ti3C2Tx composite catalyst to regulate its structure and stability, the problem of catalysts being susceptible to oxidation and degradation in the prior art is solved, and its photocatalytic activity and stability are significantly improved, and the efficient performance of hydrogen production in photocatalytic oxidation of benzyl alcohol is achieved.
Patent Information
- Application Number
- CN202510025355.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing CdS-Ti3C2Tx MXene composite catalysts are susceptible to oxidation and degradation during photocatalysis, resulting in reduced performance and shortened cycle life, and poor interface recombination effect and poor stability.
By regulating the specific surface area, number of mesoporous pores and stability of the CdS-Ti3C2Tx-BME composite photocatalyst using β-mercaptoethanol (BME), the -SH of BME forms a strong bond with unsaturated Ti atoms, inhibiting the oxidation of Ti3C2Tx and improving the photostability of the catalyst.
The photocatalytic activity and stability of the CdS-Ti3C2Tx-BME composite photocatalyst is significantly improved, the cycle life is extended, and it shows high activity, selectivity and stability in the process of photocatalytic oxidation of benzyl alcohol while producing hydrogen.
Smart Images

Figure HDA0005232562890000011 
Figure HDA0005232562890000012 
Figure HDA0005232562890000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of photocatalysts, and specifically relates to a CdS-Ti 3 C 2 T x -BME composite photocatalyst, preparation method thereof and application in photocatalytic oxidation of benzyl alcohol and simultaneous hydrogen production. Background Art
[0002] Solar energy has the advantages of being pollution-free, easily accessible, green and sustainable. Using semiconductor photocatalytic technology to convert solar energy into hydrogen energy and other chemical energy for storage has become an important research object for solving the energy and environmental problems in the world today. Photocatalytic oxidation of BA to BAD and the simultaneous production of hydrogen can make full use of the redox ability of holes and electrons, improve the utilization rate and reaction efficiency of photogenerated carriers, and has important research significance and broad application prospects. CdS, as a binary metal semiconductor compound, is widely used in the field of photocatalytic research due to its advantages such as visible light response, suitable energy band position, easily regulated morphology, low cost and stable physicochemical properties. MXene is widely used to improve the photocatalytic performance of semiconductor CdS due to its many outstanding properties, including many surface hydrophilic functional groups (-OH and -O), which enable it to easily establish a strong connection with various semiconductors, excellent metallic conductivity to ensure effective charge carrier transfer, exposed terminal metal sites and reactive sites, etc. However, MXene reacts slowly with water and dissolved oxygen, and degrades through oxidation over time. The structural and functional properties of MXene are gradually damaged, resulting in performance degradation and shortened cycle life. In addition, conventional CdS-Ti 3 C 2 T x MXene composite catalysts still have problems such as poor interface composite effect and poor stability. Therefore, how to use surfactants to delay the oxidation reaction of MXenes to further improve the performance of CdS-Ti 3 C 2 T x The photocatalytic activity and stability of the composite catalyst to achieve efficient oxidation of BA to BAD and simultaneous hydrogen production urgently require further research. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a CdS-Ti 3 C 2 T x -BME composite photocatalyst and its preparation method and application. The composite catalyst consists of a two-dimensional (2D) ultra-thin layered structure Ti 3 C 2 Tx (MXene) and its surface tightly fixed with small zero-dimensional (0D) CdS nanospheres. The present invention uses β-mercaptoethanol (BME) to regulate the composite catalyst CdS-Ti 3 C 2 T x -Specific surface area, number of mesopores and Ti content in BME composite catalysts 3 C 2 T x The -SH of BME preferentially forms strong bonds with unsaturated Ti atoms to inhibit the 3 C 2 T x -MXene component to resist the oxidation of O during photocatalysis 2 and H 2 O erosion greatly improves the CdS-Ti 3 C 2 T x -The photostability of the BME composite photocatalyst. The composite photocatalyst is used for photocatalytic selective oxidation of benzyl alcohol and simultaneous hydrogen production, and has high photocatalytic activity, selectivity and stability.
[0004] The technical solution adopted by the present invention to solve the above-mentioned problems is: A CdS-Ti 3 C 2 T x -The preparation method of BME composite photocatalyst, the specific steps are as follows: (1) Add LiF and Ti into hydrochloric acid solution respectively. 3 AlC 2 To obtain a mixed solution, the mixed solution is heated and stirred in an oil bath, washed and centrifuged to obtain MXene after the oil bath ends, and then the MXene is ultrasonically dispersed in water, and the precipitate is removed by centrifugation to obtain a MXene aqueous solution; (2) Add BME to the MXene aqueous solution obtained in step (1), sonicate in an ice-water bath for 6 min, remove impurities floating on the surface, mix with thiourea, cadmium nitrate, and ethylenediamine, stir evenly, and transfer to a hydrothermal reactor for solvothermal reaction; (3) After the solvothermal reaction is completed, CdS-Ti is obtained after washing and drying. 3 C 2 T x -BME composite photocatalyst.
[0005] According to the above scheme, in step (1), the concentration of HCl in the hydrochloric acid aqueous solution is in the range of 8-10 mol / L.
[0006] According to the above scheme, in step (1), the concentration of MXene in the MXene aqueous solution is in the range of 500-530 mg / L, and the volume of the MXene aqueous solution added during preparation is in the range of 0-14 mL.
[0007] According to the above scheme, in step (2), the molar ratio of cadmium nitrate to thiourea is 1:(1-3), and the concentration ranges of cadmium nitrate and thiourea in the aqueous solution of ethylenediamine are 0.04-0.06 mol / L and 0.03-0.05 mol / L, respectively; the temperature range of the solvothermal reaction is 150-170 °C, and the time range is 20-30 h.
[0008] According to the above scheme, in step (2), the amount of MXene aqueous solution added is no more than 6% based on the mass percentage of MXene to CdS.
[0009] According to the above protocol, in step (2), the volume added during BME preparation ranges from 30 to 120 μL.
[0010] According to the above scheme, in step (3), washing is performed using deionized water and anhydrous ethanol, and drying is performed using vacuum drying.
[0011] CdS-Ti prepared by the above method 3 C 2 T x -BME composite photocatalyst can be used in the photocatalytic oxidation of benzyl alcohol and simultaneous hydrogen production. The specific application method is: CdS-Ti 3 C 2 T x -BME composite photocatalyst is added to an acetonitrile solution of benzyl alcohol, ultrasonically dispersed or stirred evenly, then nitrogen atmosphere is introduced, and visible light irradiation is performed under sealed conditions to achieve photocatalytic oxidation of benzyl alcohol into benzaldehyde and simultaneous hydrogen production; the wavelength of visible light is greater than or equal to 420 nm, and the irradiation time is within 20 h; in the acetonitrile solution of benzyl alcohol, the concentration of benzyl alcohol is preferably 0-2 μL / mL, and the concentration of the composite photocatalyst in the acetonitrile solution of benzyl alcohol is preferably 1-5 mg / mL.
[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is in the CdS-Ti 3 C 2 T x -BME composite photocatalyst preparation, BME was added during the solvothermal process to regulate the CdS-Ti 3 C 2 T x -Specific surface area, number of mesopores and Ti content in BME composite catalysts 3 C 2 Tx The -SH of BME preferentially forms strong bonds with unsaturated Ti atoms to inhibit the 3 C 2 T x -MXene component to resist the oxidation of O during photocatalysis 2 and H 2 O erosion greatly improves the CdS-Ti 3 C 2 T x -BME composite photocatalyst photocatalytic activity and stability.
[0013] 2. CdS-Ti of the present invention 3 C 2 T x -BME composite photocatalyst, under visible light (λ≥420 nm), uses benzyl alcohol as a reaction substrate to consume photogenerated holes to generate benzaldehyde, while using photogenerated electrons to reduce protons in benzyl alcohol to produce hydrogen. This photocatalytic reaction process not only does not consume sacrificial agents but also makes full use of photogenerated carriers and converts organic matter into value-added chemicals. 3 C 2 T x -BME has better activity in photocatalytic oxidation of organic matter and simultaneous hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The urchin-shaped CdS nanospheres prepared in Example 1 and the composite photocatalyst CdS-1%Ti prepared in Example 2 are shown in FIG. 3 C 2 T x (referred to as CdS-0.3T), CdS-4%Ti 3 C 2 T x (referred to as CdS-T), CdS-5%Ti 3 C 2 T x (abbreviated as CdS-1.3T) The comparison of hydrogen production of photocatalytic BA oxidation in the first three hours (Figure a) and the comparison of the production of photocatalytic BA oxidation products and BA conversion rate (Figure b); Among them, x%Ti 3 C 2 T x x% indicates Ti 3 C 2 T x The percentage of the mass of the sea urchin-shaped CdS nanospheres.
[0015] Figure 2The composite photocatalyst CdS-T prepared in Example 2 and the composite photocatalyst CdS-4%Ti prepared in Example 2 are shown in FIG. 3 C 2 T x -0.5BME (abbreviated as CdS-T-0.5B), CdS-4%Ti 3 C 2 T x -BME (abbreviated as CdS-TB), CdS-4%Ti 3 C 2 T x -1.3BME (abbreviated as CdS-T-1.3B) H of BA oxidation in the first three hours 2 Comparison of yield, benzaldehyde yield, benzyl alcohol conversion, and benzaldehyde selectivity.
[0016] Figure 3 The H of the composite photocatalyst CdS-TB prepared in Example 1 and the composite photocatalyst CdS-T prepared in Comparative Example 2 in the photocatalytic BA oxidation (3 h) cycle experiment 2 Comparison of yields (Fig. a) and BA conversion rates of the photocatalytic BA oxidation (3 h) cycle experiment. DETAILED DESCRIPTION
[0017] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0018] A method for preparing sea urchin-shaped CdS nanospheres, the specific steps are as follows: 1.1 mmol cadmium nitrate tetrahydrate (Cd(NO 3 ) 2 ·4H 2 O) and 2.1 mmol thiourea (CN 2 H 4 The urchin-shaped CdS nanospheres were obtained by dissolving the precipitated CdS in 14 mL of deionized water and mixing it with 25 mL of ethylenediamine solution. The mixture was stirred evenly and then transferred to a 50 mL reactor for solvothermal reaction at 160 °C for 24 h. The precipitated CdS nanospheres were then centrifuged at 7000 rpm, washed twice with deionized water, once with anhydrous ethanol, and dried at 60 °C for 12 h to obtain urchin-shaped CdS nanospheres.
[0019] The above-mentioned sea urchin-shaped CdS nanospheres are used for photocatalytic oxidation of benzyl alcohol and simultaneous hydrogen production. The specific application process is as follows: 5 mL of acetonitrile, 5 μL of BA, and 10 mg of sea urchin-shaped CdS nanospheres were placed in a reaction tube, mixed evenly after ultrasonic treatment for 2 min, and nitrogen was introduced for 15 min to expel oxygen. After nitrogen was introduced, the reaction tube was sealed and irradiated with visible light (λ≥420 nm) for 3 h. Every 1 h, 1 mL of the gas in the tube was injected into a gas chromatograph to detect the production of hydrogen. After irradiation for 3 h, the supernatant was filtered out and placed in the liquid autosampler of the gas chromatograph to detect the contents of BA and BAD in the supernatant.
[0020] A CdS-Ti 3 C 2 T x The preparation method of the composite photocatalyst comprises the following specific steps: (1) Add 1 g LiF and 1 g Ti in small amounts to 10 mL of 9 mol / L hydrochloric acid solution. 3 AlC 2 The mixed solution was placed in a 35 °C oil bath and heated and stirred for 24 h, then washed with water until the pH of the supernatant was greater than 6, and then centrifuged at a speed of 10000 rpm to obtain Ti 3 C 2 T x (MXene), MXene is ultrasonically dispersed in water, and the precipitate is removed by centrifugation at a speed of 3500 rpm to obtain a MXene aqueous solution; (2) Add 4.6 mL of deionized water and 1.1 mmol of cadmium nitrate tetrahydrate (Cd(NO 3 ) 2 ·4H 2 O) and 2.1 mmol thiourea (CN 2 H 4 S) and 25 mL of ethylenediamine solution, stirring for 30 min to form a homogeneous solution; (3) The above uniform solution was transferred to a 50 mL reactor and subjected to solvothermal reaction at 160 °C for 24 h. The solution was then centrifuged at 7000 rpm, washed twice with deionized water, once with anhydrous ethanol, and dried at 60 °C for 12 h to obtain CdS-Ti 3 C 2 T x Composite photocatalyst.
[0021] In this step, the concentration of the MXene aqueous solution is 520 mg / L, the volume of the added MXene aqueous solution is 9.4 mL, and the mass percentage of MXene contained relative to 0.12 g CdS nanospheres is 4%.
[0022] (4) Changing the amount of MXene aqueous solution in step (2) to prepare CdS-x%Ti 3 C 2 T x , where x%Ti 3 C 2 T x Ti 3 C 2 T x The percentage of the mass of the sea urchin-shaped CdS nanospheres (x=1%, 4%, 5%) was used to obtain CdS-0.3T, CdS-T, and CdS-1.3T.
[0023] The above CdS-x%Ti 3 C 2 T x The composite photocatalyst is used for photocatalytic oxidation of benzyl alcohol and simultaneous production of hydrogen. The specific application process is as follows: Take 5 mL of acetonitrile solution, 5 μL of BA, 10 mg of CdS-x%Ti 3 C 2 T x The composite photocatalyst was placed in a reaction tube and mixed evenly after ultrasonic treatment for 2 min, and nitrogen was introduced for 15 min to exhaust the oxygen. After nitrogen was introduced, the reaction tube was sealed and irradiated with visible light (λ≥420 nm) for 3 h. Every 1 h, 1 mL of the gas in the tube was taken and injected into a gas chromatograph to detect the hydrogen production. After irradiation for 3 h, the supernatant was filtered out and placed in a liquid autosampler for gas chromatography to detect the contents of BA and BAD in the supernatant.
[0024] like Figure 1 As shown, loading different amounts of MXene on CdS by a hydrothermal method can improve its performance in photocatalytic oxidation of BA and simultaneous hydrogen production, and the optimal MXene loading ratio was determined to be 4% (the percentage of the mass of MXene relative to the mass of CdS). Example
[0025] A CdS-Ti 3 C 2 T x -The preparation method of BME composite photocatalyst, the specific steps are as follows: (1) Add 1 g LiF and 1 g Ti in small amounts to 10 mL of 9 mol / L hydrochloric acid solution. 3 AlC 2To obtain a mixed solution, the mixed solution is placed in a 35 °C oil bath for heating and stirring for 24 h, and then washed with water until the pH of the supernatant is greater than 6. Next, centrifugation is performed at a speed of 10,000 rpm to obtain MXene. The MXene is ultrasonically dispersed in water, and the precipitate is removed by centrifugation at a speed of 3,500 rpm to obtain a MXene aqueous solution. (2) Add 4.5 mL of deionized water and 86 μL of β-mercaptoethanol to 9.4 mL of MXene aqueous solution, sonicate in an ice-water bath for 6 min, remove the impurities floating on the surface, and then add 1.1 mmol of cadmium nitrate tetrahydrate (Cd(NO 3 ) 2 ·4H 2 O), 2.1mmol thiourea (CN 2 H 4 S) and 25 mL of ethylenediamine solution were mixed and stirred for 30 min to form a homogeneous solution; (3) The above uniform solution was transferred to a 50 mL reactor, and the solvent thermal reaction was carried out at 160 °C for 24 h, and then centrifuged at 7000 rpm, washed twice with deionized water, washed once with anhydrous ethanol, and dried at 60 °C for 12 h to obtain a CdS-TB composite catalyst. In this step, the concentration of the MXene aqueous solution was 520 mg / L, and the mass percentage of MXene contained was 4% relative to the mass percentage of 0.12 g CdS nanospheres; the volume of β-mercaptoethanol was 86 μL.
[0026] (4) Changing the amount of BME added in step (3) to prepare CdS-Ti 3 C 2 T x -yBME (abbreviated as CdS-T-yB) composite photocatalyst (y in yBME represents the volume of BME in the composite catalyst is y μL, y=43, 86, 115 μL), and CdS-T-0.5B, CdS-TB, and CdS-T-1.3B composite photocatalysts were obtained.
[0027] The above CdS-TB composite photocatalyst is used for photocatalytic oxidation of benzyl alcohol and simultaneous production of hydrogen. The specific application process is as follows: 5 mL of acetonitrile, 5 μL of BA, and 10 mg of CdS-TB photocatalyst were placed in a reaction tube, mixed evenly after ultrasonic treatment for 2 min, and nitrogen was introduced for 15 min to exhaust oxygen. After nitrogen was introduced, the reaction tube was sealed and irradiated with visible light (λ≥420 nm) for 20 h; 1 mL of the gas in the tube was taken at regular intervals and injected into a gas chromatograph to detect the production of hydrogen. When the photocatalytic reaction reached equilibrium, the supernatant was collected by filtration, and the content of the remaining BA and the content of the generated BAD were detected in the supernatant using an automatic liquid phase injector of a gas chromatograph.
[0028] like Figure 2 As shown in Figure 2, with the increase of BME content, the composite catalyst CdS-Ti 3 C 2 T x -yBME performance continued to improve; when BME was excessive, the performance of the composite catalyst CdS-T-1.3B decreased. After 3 h of illumination, the photocatalytic BA oxidation dehydrogenation of the composite catalysts CdS-T-0.5B and CdS-TB using BME continued to increase, and always had higher BA oxidation dehydrogenation and dehydrogenation rates than the composite catalyst CdS-T without BME. Among the composite catalysts with added BME, CdS-TB was the composite catalyst with the best performance, proving that the photocatalytic oxidation performance of the composite catalyst CdS-T can be further improved by adjusting the amount of BME added.
[0029] like Figure 3 As shown in the figure, the photostability of CdS-TB composite catalyst was studied by photocatalytic redox cycling experiments. After five cycles, the H 2 The yield and BA conversion decreased by about 36% and 42%, respectively, while CdS-TB showed an almost stable H 2 The results show that the addition of BME makes the CdS-TB composite material more efficient in the photocatalytic process of O 2 and H 2 The photocatalytic performance of the photocatalysts is better than that of the O2-doped photocatalysts, which makes them more resistant to O2 corrosion, thus improving their stability during the photocatalytic process.
[0030] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A CdS-Ti3C2T x -A method for preparing a BME composite photocatalyst, characterized in that: The main steps are as follows: (1) LiF and Ti3AlC2 are added to a hydrochloric acid solution to obtain a mixed solution, and the mixed solution is heated and stirred in an oil bath. After the oil bath ends, the mixed solution is washed and centrifuged to obtain MXene, and then the MXene is ultrasonically dispersed in water. After the precipitate is removed by centrifugation, the MXene aqueous solution is obtained; (2) Add BME to the MXene aqueous solution obtained in step (1), sonicate in an ice-water bath for 6 min, remove impurities floating on the surface, mix with thiourea, cadmium nitrate, and ethylenediamine, stir evenly, and transfer to a hydrothermal reactor for solvothermal reaction; (3) After the solvothermal reaction is completed, CdS-Ti3C2T is obtained after washing and drying. x -BME composite photocatalyst.
2. A CdS-Ti3C2T according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (1), the concentration of HCl in the hydrochloric acid solution is in the range of 8-10 mol / L.
3. A CdS-Ti3C2T3 according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (1), the concentration of MXene in the MXene aqueous solution is in the range of 510-530 mg / L, and the volume of the MXene aqueous solution added during the preparation is in the range of 0-14 mL.
4. A CdS-Ti3C2T according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (2), the molar ratio of cadmium nitrate to thiourea is 1:(1-3), and the concentrations of cadmium nitrate and thiourea in the aqueous solution of ethylenediamine are in the range of 0.04-0.06 mol / L and 0.03-0.05 mol / L, respectively; the temperature range of the solvothermal reaction is 150-170 °C, and the time range is 20-30 h.
5. A CdS-Ti3C2T3 according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (2), the amount of MXene aqueous solution added is calculated as the mass percentage of MXene to CdS and is not more than 6%.
6. A CdS-Ti3C2T3 according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (2), the volume added during BME preparation ranges from 30 to 120 μL.
7. A CdS-Ti3C2T3 according to claim 1 x -A method for preparing a BME composite photocatalyst, characterized in that: In step (3), washing is performed using deionized water and anhydrous ethanol, and drying is performed using vacuum drying.
8. CdS-Ti3C2T prepared by the method according to any one of claims 1 to 7 x -BME composite photocatalyst.
9. The CdS-Ti3C2T3 according to claim 8 x -Application of BME composite photocatalyst in photocatalytic oxidation of benzyl alcohol and simultaneous hydrogen production.
10. The use according to claim 9, characterized in that The specific application method is: CdS-Ti3C2T x -BME composite photocatalyst is added to an acetonitrile solution of benzyl alcohol, and after ultrasonic dispersion, a nitrogen atmosphere is introduced and visible light irradiation is performed under sealed conditions to achieve photocatalytic oxidation of benzyl alcohol into benzaldehyde and simultaneous hydrogen production; wherein the wavelength of visible light is not less than 420 nm and the irradiation time is not more than 20 h.